Types of Implicatures Hate Speech TikTok Social Media - Afni Sigalingging; Martina Girsang; Charles David Marudut Silalahi (Winaya Inspirasi Nusantara Foundation, 2025)
Background of the problem: Communication in social networks and everyday life, we use language as a means of communication. Language is a tool of interaction or communication, which is a tool to convey thoughts, ideas, concepts, and emotions. Language is also considered a system of symbols in the form of sounds that are arbitrary, agile, dynamic, diverse, and humanized. Language is a communication tool to convey messages to others, and through language, humans can interact with others. Purpose: The objectives of this research are to identify the types of implicature’s contained in hate speech in the TikTok social media comment section. Method: The research method used by researchers in this study is a qualitative approach using a descriptive type. Documentation technique is a technique where data obtained for research needs comes from existing documents on written objects, books, pictures, which are related to the object of research. In this study, the documentation used is by taking documentation in the form of screenshots or screenshots of uploads or comments found on social media TikTok. Result: As a result of this research, the author concludes that there are two types of implicature, including 1) conversational implicature and 2) conventional implicature. Implication: This study provides insight into how implicatures, both conversational and conventional, are used in hate speech on social media. This study contributes to the broader field of pragmatics by illustrating how language functions in digital communication.